PKM KELOMPOK LANJUT USIA, DALAM PENINGKATAN PENGETAHUAN REMATIK DAN LATIHAN SENAM REMATIK DI WILAYAH KERJA PUSKESMAS MACCINI SAWAH MAKASSAR - Ekayanti Hafidah Ahmad; Ricky Zainuddin; Sanghati; Erna Kasim; Nurbaiti; Andi Arniyanti; Ain Zakaria; Jailani Tilitu (Stikes Panrita Husada Bulukumba, 2023)
In old age a person will find some changes that must be faced. These changes include the decline in function of the respiratory, cardiovascular and musculoskeletal systems. An initial survey conducted in the Work Area of ​​the Maccini Sawah Health Center in Makassar, South Sulawesi Province found that most of the elderly had arthritis. Problems faced at this time Most of the elderly still lack knowledge about rheumatism, do not understand how to treat or treat rheumatism, and information communication media such as leaflets/brochures are still lacking. Target and outcome: apart from journal output, the target in this community service is to carry out health education activities for the elderly about the management of rheumatism by doing elderly gymnastics to prevent rheumatism. Methods of implementation include education about rheumatism, routine rheumatic gymnastics together. It is hoped that health workers in the working area of ​​the Maccini Sawah Health Center can monitor, motivate and improve the health of the elderly through periodic health promotion activities, especially regarding rheumatism.